English Conversation Teaching by Pairwork Technique for The First Year English Majored Students - Dalimunte, Muhammad (Association of Language Teachers in Southeast Asia (ALTSA), 2018)
This research applied Classroom Action Research (CAR) to know if Pair-work technique is appropriate used to teach English Conversation. This research was conducted in two cycles of teaching learning activities, it was attained that the students’ ability at speaking could be increased which found the students’ test scores from pre-cycle (before doing treatment) to the second cycle (after the treatment done) increased. In the pre-test denoted that 78.1% (25 students of 32 research subjects) got scores below 70, in the post-test of cycle one was attained 90,6% (29 students of 32 research subjects) got scores 70 up and in the cycle two- post test 93,75% of the students got scores 70 up. This strategy could also drive the students actively taking part in the classroom